2021
DOI: 10.1530/vb-20-0013
|View full text |Cite
|
Sign up to set email alerts
|

The aging endothelium

Abstract: Cellular senescence is now recognised as one of the hallmarks of ageing. Herein, we examine current findings on senescence of the vascular endothelium and its impacts on age-related vascular diseases. Endothelial senescence can result in systemic metabolic changes, implicating senescence in chronic diseases such as diabetes, obesity and atherosclerosis. Senolytics, drugs that eliminate senescent cells, afford new therapeutic strategies for control of these chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 146 publications
0
15
0
Order By: Relevance
“…In old mice (>12 months), vessel dysfunction is accompanied by irreversible histological changes characterized by atherosclerotic plaques and vascular wall remodelling [ 19 ]. In the present study, a relatively early advanced life span was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In old mice (>12 months), vessel dysfunction is accompanied by irreversible histological changes characterized by atherosclerotic plaques and vascular wall remodelling [ 19 ]. In the present study, a relatively early advanced life span was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…29 The endothelium that dies prematurely cannot be efficiently repopulated, resulting in microvessels devoid of endothelium, the critical stimulus for basement membrane zone reduplication. 30 A procoagulant state in the context of CCV has been previously reported in the literature, specifically in a middle-aged woman with a history of prothrombin G20210A thrombophilia and biopsy-proven CCV. 31 Vascular thrombosis is a stimulus to endogenous nitrous oxide release from endothelium and leads to vascular relaxation hallmarked by vascular dilatation.…”
Section: Discussionmentioning
confidence: 79%
“…Inhibition of endothelial growth leading to CCV helps support the concept that a diminished endothelial cell progenitor pool might be a key event 29 . The endothelium that dies prematurely cannot be efficiently repopulated, resulting in microvessels devoid of endothelium, the critical stimulus for basement membrane zone reduplication 30 …”
Section: Discussionmentioning
confidence: 82%
“…Clinical trials have shown that targeting inflammation can reduce cardiovascular events [ 317 ]. The healthy vascular endothelium inhibits platelet adhesion to the surface [ 325 ] but cardiovascular risk factors (e.g., hypertension) increase oxygen free radical production, causing the endothelium to switch to a pro-coagulant, pro-inflammatory and vasoconstrictor phenotype [ 326 , 327 ].…”
Section: Resultsmentioning
confidence: 99%